The Really Useful Physical Education Book : Learning and Teaching Across the 7-14 Age Range - Edited By Gary Stidder and Sid Hayes (London Routledge Taylor & Francis Group, 2011)
Provides training and practicing teachers with guidance and ideas to teach physical education effectively at Key Stage 2 and Key Stage 3. This title offers ideas for learning and teaching a range of activities: games; gymnastics; dance; swimming and water-based activities; athletics; on-site outdoor and adventurous activities; and, more.
Includes Reference. Illustrations and Index.
Keywords: Physical Education and Training--Curricula -- Physical Education and Training--Study and Teaching -- Great Britain